2021
DOI: 10.3390/antiox10091402
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Protective Effect of Young Barley (Hordeum vulgare L.) Dietary Supplements Extracts on UV-Treated Human Skin Fibroblasts in In Vitro Studies

Abstract: Young barley seems to be a promising material for use as nutricosmetic due to the presence of many biologically active compounds. The aim of this study was to evaluate the effect of Hordeum vulgare L. extracts on human skin fibroblasts exposed to ultraviolet radiation B (UVB) radiation. Analysis of the chemical composition showed a predominance of 9,12,15-octadecatrienoic acid. The quality assessment showed that young barley preparations have high total polyphenolic content (TPC) and favourable total antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Furthermore, data collected by Czerwonka et al were obtained after a shorter time of HSF exposure to barley products (24 h), and the cell toxicity was determined using a different method (neutral red assay). Due to the similar time of cells treatment (48 h) as well as used assays (MTT and BrdU test), it is worth mentioning the reaserch by Gromkowska-Kępka et al, who also showed that the water extract of young barley juice at concentrations ranging from 5 -100 µg/ml did not alter the proliferation of normal human skin fibroblasts (NHSF) [21]. Robles-Escajeda et al, who investigated the water extract obtained from the powder of barley young leaves of Hordeum vulgare in human dermal neonatal foreskin Hs27 fibroblasts, revealed that the tested extract at concentration of 1500 µg/ ml was not cytotoxic (assessment after 24 h of cell treatment; flow cytometry of cells stained with propidium iodide), and did not alter fibroblast proliferation (investigation after 96 h of cell treatment; cell counting) [13].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, data collected by Czerwonka et al were obtained after a shorter time of HSF exposure to barley products (24 h), and the cell toxicity was determined using a different method (neutral red assay). Due to the similar time of cells treatment (48 h) as well as used assays (MTT and BrdU test), it is worth mentioning the reaserch by Gromkowska-Kępka et al, who also showed that the water extract of young barley juice at concentrations ranging from 5 -100 µg/ml did not alter the proliferation of normal human skin fibroblasts (NHSF) [21]. Robles-Escajeda et al, who investigated the water extract obtained from the powder of barley young leaves of Hordeum vulgare in human dermal neonatal foreskin Hs27 fibroblasts, revealed that the tested extract at concentration of 1500 µg/ ml was not cytotoxic (assessment after 24 h of cell treatment; flow cytometry of cells stained with propidium iodide), and did not alter fibroblast proliferation (investigation after 96 h of cell treatment; cell counting) [13].…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced antioxidant activity affects the potential of young barley leaves and products derived from them. Gromkowska-Kępa et al demonstrated that barley leaves rich in antioxidants exhibit high protective activity against high-energy UV radiation acting on human skin fibroblasts [30]. Ali et al (2014) conditioned fresh papaya fruit by applying fumigation with gaseous O 3 (0, 1.5, 2.5, 3.5 and 5 ppm) continuously for 96 h before the material was stored at 25 • C. After 10 days of storage, they found that the fruit exposed to O 3 at a rate of 2.5 ppm presented 30.9% higher antioxidant activity compared to the material which was not treated with ozone [31].…”
Section: Resultsmentioning
confidence: 99%
“…(Ekanayake-Mudiyanselage et al, 2005) [43] 6. Trace elements Cu Grain (Obadi et al, 2021; Gromkowska-Kępka et al, 2021) [28,44] Copper, Zinc, and selenium are antioxidants. (Gromkowska-Kępka et al, 2021) [44] Zn Zinc is used orally to treat acne, alopecia, rheumatoid arthritis.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%
“…Trace elements Cu Grain (Obadi et al, 2021; Gromkowska-Kępka et al, 2021) [28,44] Copper, Zinc, and selenium are antioxidants. (Gromkowska-Kępka et al, 2021) [44] Zn Zinc is used orally to treat acne, alopecia, rheumatoid arthritis. Local use of zinc promotes wound healing and reduces inflammation.…”
Section: Vitamins and Mineralsmentioning
confidence: 99%